Different penal climates in Europe - Krajewski, Krzysztof (Kriminologijos studijos, 2014)
The European ‘penal climate’ is defined by consistent patterns of difference in penal policies that are well known and well documented. One such pattern involves differences between ‘old’ EU member states in Western Europe and ‘new’ EU member states, in Central and Eastern Europe. The two above zones of European ‘penal climate’ differ not only in the severity of sanctions imposed (as measured by imprisonment rate, average length of prison sentences, and average time spent in prison), but also in other characteristics of sentencing patterns, including types of sanctions used and their structure. This paper presents selected statistical data regarding differences in penal policies implemented in Western and Central and Eastern Europe, compared with the police data on registered offences. Comparison of the two data sets gives insight to the state of crime control policies in European countries.Key words: penal climate – penal policy – punitiveness – imprisonment rate – alternatives to imprisonment